The representation of mesmerism in Honoré de Balzac's La comédie humaine - Marcus, K. Melissa (New connections, 1995)
In 1778, the Austrian physicians, Franz Anton Mesmer, arrived in Paris to present his new doctrine: animal magnetism, later called mesmerism. His stay in Paris provoked a lasting interest in, and fascination with mesmerism, in particular among various circles of European Romantic writers. This book treats the theme of mesmerism in French writer Balzac's La comedie humaine by demonstrating how Balzac acts as "literary healer," given his belief in the healing power of mesmerism